1998
DOI: 10.1597/1545-1569_1998_035_0154_dpopap_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of Primary and Permanent Dentition in Children with Unilateral Complete Cleft Lip and Palate

Abstract: Objective To investigate the distribution patterns of primary and permanent teeth in the cleft area and the numerical variation in teeth in unilateral complete cleft lip and palate (UCLP) patients. Design A survey of the dentition in UCLP patients. Setting Craniofacial Center, Chang Gung Memorial Hospital, Taipei, Taiwan. Patients 137 UCLP patients who met the following criteria: (1) have had at least one panoramic film taken, (2) the first panoramic film illustrates either primary or early mixed dentition. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
4
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 14 publications
4
65
4
3
Order By: Relevance
“…It carries two upper central and two lateral incisors. During embryogenesis, however, the maxillary processes also provide material to the prospective premaxilla in humans, and the incisive suture between the maxilla and premaxilla bones does not have to be located in the area of the previous fusion of the medial nasal and maxillary processes but instead can be located more posteriorly (Lisson & Kjaer, 1997;Tsai et al 1998;Barteczko & Jacob, 2004). Indeed, two subcomponents of the premaxillathe *Anlage represents an embryonic area capable of forming a structure, i.e.…”
Section: The Early Prenatal Development Of Human Jawsmentioning
confidence: 99%
See 1 more Smart Citation
“…It carries two upper central and two lateral incisors. During embryogenesis, however, the maxillary processes also provide material to the prospective premaxilla in humans, and the incisive suture between the maxilla and premaxilla bones does not have to be located in the area of the previous fusion of the medial nasal and maxillary processes but instead can be located more posteriorly (Lisson & Kjaer, 1997;Tsai et al 1998;Barteczko & Jacob, 2004). Indeed, two subcomponents of the premaxillathe *Anlage represents an embryonic area capable of forming a structure, i.e.…”
Section: The Early Prenatal Development Of Human Jawsmentioning
confidence: 99%
“…5I) of the lateral incisor can also occur. Tsai et al (1998) have described four different patterns for the location of the deciduous lateral incisor in patients affected by a complete cleft lip and palate, depending on the location of the lateral incisor with regard to the position of the cleft (Fig. 5F-I).…”
Section: The Dual Origin Of the Upper Lateral Incisor Explains Its Dementioning
confidence: 99%
“…The upper lateral incisor is the most frequently affected tooth in the cleft area both in primary (circa 10%) and in permanent (circa 50%) dentitions. A higher incidence of dental agenesis outside the cleft region, more in particular involving the permanent maxillary dentition, has also been reported (5, 255–258) and suggestion has been made to distinguish clefting associated with dental agenesis from clefting occurring alone (150, 259). Successive linkage analysis studies have indicated involvement in non‐syndromic CL/CLP of different loci, mapped respectively to chromosome 6p24 (OFC1, Orofacial cleft‐1; OMIM Entry 119530) (260–262), 2p13 (OFC2; OMIM Entry 602966), 19q13 (OFC3; OMIM Entry 600757), and regions on 4q (OFC4; OMIM Entry 608371).…”
Section: Human Tooth Agenesis: a Complex Genetic Traitmentioning
confidence: 99%
“…Tooth anomalies represent an interesting chapter of orofacial pathology, for both their aetiological background and clinical implications. Several studies [1][2][3][4][5][6][7][8][9] have demonstrated that dental anomalies in number, size, shape, timing of formation, eruption and enamel dysplasia are more frequent in children affected by cleft lip, cleft palate or both (CLP) than in the general population. These studies showed that both primary and permanent dentitions can be affected, and that the dental anomalies are more frequent on the cleft side of the maxilla.…”
Section: Introductionmentioning
confidence: 99%
“…Missing or supernumerary teeth, and delayed dental development are the most common types of dental anomalies observed. In CLP subjects, the lateral incisor in the region of the alveolar cleft is very sensitive to developmental disorders 1,[3][4][5] . Some authors 1,4,[6][7][8][9] claim that teeth outside the cleft area are also affected more frequently than in children without CLP.…”
Section: Introductionmentioning
confidence: 99%